The Peculiarities of the Budgetary Policy of Georgia and the Directions of Improvement in Association with EU - George Abuselidze; Linda Mamuladze (SHS Web of Conferences, 2020)
The work deals with the role of budgetary policy on socioeconomic development of the country, the practical significance of budgetary policy improvement, the peculiarities of program financing, the problems of rationalization of budget resources, the existing reality and the main directions of improvement the effectiveness. The aspects of research are compared to the advanced international practice. The research is focused on the problems and the anti-rational usage of budget funds in the budgetary process, the peculiarities and efficiency of forming the program budget, the problems in the formation of expected results and budget performance indicators of the programs/sub-programs.
Keywords: F36; H61; H76; H87; 330; Budget Policy; Budget Planning; Program Budget; Effectiveness; Georgia; EU